Financial literacy and savings account returns - Florian Deuflhard; Dimitris Georgarakos; Roman Inderst (Goethe University Frankfurt, Institute for Monetary and Financial Stability (IMFS), 2015)
Savings accounts are owned by most households, but little is known about the performance of households' investments. We create a unique dataset by matching information on individual savings accounts from the DNB Household Survey with market data on account-specific interest rates and characteristics. We document considerable heterogeneity in returns across households, which can be partly explained by financial sophistication. A one-standard deviation increase in financial literacy is associated with a 13% increase compared to the median interest rate. We isolate the usage of modern technology (online accounts) as one channel through which financial literacy has a positive association with returns.
urn:nbn:de:hebis:30:3-374802
Keywords: D12; E21; G11; G21; 330; financial literacy; savings accounts; interest rates; household finance